Patient-related factors associated with medication adherence behavior in patients with end-stage renal disease: a systematic review - Ooi, Peiboon; Abdul Latif, Anisa'lliya; Lee, Kaiwei; Phang, Kelly; Abdul Rashid, Aneesa; Chan, Neenee; Peh, Suatcheng; Thilaganathan, Thiruventhiran (Medknow, 2022)
Objectives: This systematic review aims to identify influencing factors of medication adherence behavior in patients with end-stage renal disease (ESRD), with a special interest in patient-related factors based on the World Health Organization adherence model. Materials and Methods: Primary electronic databases comprising PubMed, Scopus, Web of Science, Embase and Cochrane Library, as well as ProQuest (Health and Medical), ProQuest (Psychology), and EBSCOHost (APA PsychARTICLES) were used to search for literature on patient-related factors in medication adherence, from inception till August 31, 2021. Results: 479 articles were identified and six articles meeting eligibility criteria were reviewed and remained in this systematic review. The present review found that despite different tools being used to measure ESRD’s perception of medication’s necessity and beliefs, there was a profound association between perception and beliefs with medication adherence behavior. There is a positive relationship between knowledge, belief, educational level, ethnicity, female, and medication adherence behavior. Mixed finding was reported between perception, age, and medication adherence behavior. However, there were no studies on patients’ attitudes and medication adherence behavior as suggested in the WHO adherence model. Conclusion: Only a limited number of patient-related factors were available for evaluation in the current systematic review. Additional research is needed to advance the understanding of medication adherence behavior affected by patient-related factors on the medication and illness. However, the findings must be taken with caution because of the limited studies included in this review.